Some spineless fósiles of Huacrapuquio, province of Huancayo, departament of Junín - Peru - Prado Velazco, Ysabel (2012)
In you Walk them of the Central Peru, in Junín, between the towns of Huacrapuquio and Huarisca, they appear calcareous of the Formación Condorsinga (Jurassic Inferior), where you gathers 7 species of spineless silicificados: Lobothyris punctata (Sowerby) braquiópodo of the Familia Terebratulidae; three bivalve, Lima (Antiquilima) succinctus Schlotheim, 1813 of the Familia Limidae; Myophorella (Myophorella) araucana (Leanza) Pérez and Kings ,1978 of the Familia Trigoniidae and, Martesia sp. Sow, 1824 Of the family Pholadidae; an equinodermo, Rhabdocidaris sp. Desor, 1855 of the Familia Rhabdocidaridae; a crinoideo, Isocrinus sp. (Von Meyer) Agassiz, 1836 of the Familia Isocrinidae; and a cefalópodo, Belemnites acuarius (Schloth.) of the Familia Belemnitidae. This association of marked cosmopolitan character, of shallow and warm seas is an evidence of the warm climate that reigned in the Jurassic one. The identified species acquire value cronoestratigráfico, for their association with amonites and they date the study area as of the Half Liásico to the Aaleniano. Litoestratigráficamente belongs to the Formación Condorsinga.